199 The Translation Procedures of Cultural Expressions Applied in â€œA Game of Thronesâ€ - Oey Vella Valencia W; Rahmanti Asmarani (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2016)
Language and culture are the main objects in a translation process. The cultural expression are often found in some kinds of text which are interested to explore. Translation procedures are needed especially in translating cultural expressions. The definition of procedure in general is a series of actions that are done in a certain way or order; an established or accepted way of doing something. This study focuses to find the translation procedures of cultural expressions applied in the target text. The descriptive qualitative method is applied to analyze the data, since the aim of the study is to find the categories of cultural expressions and the translation procedures applied the most in the cultural words found in A Game of Thrones novel. The framework by Peter Newmark is applied for examining the data. Based on the analysis that has been conducted, the cultural category found the most in A Game of Thrones novel is ecology and the least cultural category found is social culture. The translation procedure mostly used is transference and the least procedure used is synonymyKeywords: Translation, Translation Procedures, Cultural Expressions, A Game of Thrones, Novel